Implementasi Enkripsi Payload menggunakan Algoritme Grain 128 berbasis IoT Middleware - Winda Ayu Safitri; Ari Kusyanti; Eko Sakti Pramukantoro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Cryptography is an attempt to secure a message by using encryption techniques and keys to find the original message. Cryptography is essential in the process of exchanging messages on the Internet of Things in order to prevent sent message stealing or manipulation. In the middleware scheme, security features have not been implemented either in data transmission or data validation, therefore, a method is needed to fill in the security gap. Solving this problem, a method can guarantee the confidentiality of the communication, which is by implementing Grain 128 algorithm. Grain 128bit algorithm can protect packets sent. The results of the study show that the 128 Grain algorithm has been successfully implemented for data payload on the MQTT and CoAP protocols. Grain 128bit algorithm that has been implemented in the research system has gone through test vector and is declared valid. Data confidentiality testing proves that the confidentiality and integrity aspects can be applied in the encryption and decryption process. An active attact testing is successfully carried out when the user entered the plaintext and knew the ciphertext, because the xor process of the plaintext and ciphertext will produce a keystream. A passive attack testing is successfully carried out because on the result of observations, the sent and received plaintext do not change. In the process of encryption, the sent data are in the form of ciphertext.